Health-related quality of life and patient-centred outcomes with COVID-19 vaccination in patients with breast cancer and gynaecological malignancies - Forster, Marie; Wuerstlein, Rachel; Koenig, Alexander; Stefan, Alexandra; Wiegershausen, Elisa; Batz, Falk; Trillsch, Fabian; Mahner, Sven; Harbeck, Nadia; Chelariu-Raicu, Anca (Frontiers in Oncology, 2023)
Introduction Safety and tolerability of COVID-19 vaccines were demonstrated by several clinical trials which led to the first FDA/EMA approvals in 2021. Because of mass immunizations, most social restrictions were waived with effects on quality of life. Therefore, our a-priori hypothesis was that COVID-19 vaccination impacted the health-related quality of life (HR-QoL) in patients with breast and gynecological cancer. Methods From March 15th until August 11th, 2022, fully vaccinated patients with breast and gynecological cancer treated in the oncological outpatient clinics of the Department of Obstetrics and Gynecology, LMU University Hospital, Munich, Germany filled out a vaccine related QoL survey. Patients were asked about demographics (age, comorbidities), clinical parameters related to previous COVID-19 infections, and HR-QoL related parameters (living situation, responsibilities in everyday life). Subsequently, a questionnaire with 12 items was designed using a 5-point Likert scale (0 – strongly disagree/4 – strongly agree), covering the aspects health and therapy, social environment, participation in everyday life and overall assessment. Results By August 11th, 2022, 108 out of 114 (94.7%) patients had received at least three doses of COVID-19 vaccine and six patients at least two doses. More than half of the surveyed patients were >55y (52.6%; mean: 55.1y, range 29-86y). Patients with breast cancer (n= 83) had early (59.0%) or metastatic cancer (41.0%); gynecological cancers (n=31) also included metastatic (54.8%) and non-metastatic cancer (45.2%). 83.3% of the patients stated that COVID-19 vaccination had a positive impact on their HR-QoL. Furthermore, 29 patients (25.4%) had undergone a COVID-19 infection. These patients reported self-limiting symptoms for a median duration of 5.9 days and no hospital admissions were registered. Conclusions Our study demonstrates that vaccination against COVID-19 was positively associated with HR-QoL in patients with breast and gynecological cancer. Furthermore, vaccinated patients who underwent COVID-19 disease experienced only self-limiting symptoms.